Study on the Emission Characteristics in Renewable Energy Combustion under Different Working Conditions of Marine Two-Stroke Diesel Engine - Ding Yang; Fang Zixian; Wang Ruolan; Shao Guoyu; Yang Kunyong (E3S Web of Conferences, 2023)
In this paper, MAN 6S35ME-B9 two-stroke diesel engine is taken as the research object. By constructing a detailed combustion reaction mechanism including CH4, C4H10O, nitrides and other substances, CHEMKIN-PRO is used to simulate the same fuel mixing ratio and excess air coefficient. Under the condition of 1.5, the temperature, NO mole fraction and NH3 mole fraction in the reactor change and study the factors affecting the pollutant emission of marine diesel engine with the crank angle under different working conditions. The simulation shows that with the decrease of diesel engine speed, the maximum temperature of combustion reaction and the temperature at exhaust opening are obviously reduced. At the same time, mole fraction of NO and NH3 decreases with the decrease of rotational speed, and there is no nitride production in the combustion reaction at 25%.